2018
DOI: 10.3389/fphar.2018.01328
|View full text |Cite
|
Sign up to set email alerts
|

Anthraquinone Emodin Inhibits Tumor Necrosis Factor Alpha-Induced Calcification of Human Aortic Valve Interstitial Cells via the NF-κB Pathway

Abstract: Exploring effective therapies for delaying calcific heart valve disease (CHVD) is the focus of current cardiovascular clinical and scientific research. In this study, human aortic valve interstitial cells (hVICs) were isolated from patients with CHVD. After expansion, cultured hVICs were induced with the tumor necrosis factor-alpha (TNF-α) with or without anthraquinone emodin (EMD) treatments. Cytotoxicity and flow cytometric analysis were used to assess cell growth, while Alizarin Red S staining was used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Moreover, CAPE has been demonstrated to inhibit NF-κB and to contribute to anti-inflammatory processes ( Celik and Erdogan, 2008 ; Nie et al., 2017 ). In our previous studies, we confirmed that inflammatory responses accelerate the formation of valvular calcification ( Xu et al., 2018 ; Huang et al., 2019 ; Xu et al., 2019a ). Therefore, we investigated the anti-calcification effect of CAPE.…”
Section: Introductionsupporting
confidence: 79%
“…Moreover, CAPE has been demonstrated to inhibit NF-κB and to contribute to anti-inflammatory processes ( Celik and Erdogan, 2008 ; Nie et al., 2017 ). In our previous studies, we confirmed that inflammatory responses accelerate the formation of valvular calcification ( Xu et al., 2018 ; Huang et al., 2019 ; Xu et al., 2019a ). Therefore, we investigated the anti-calcification effect of CAPE.…”
Section: Introductionsupporting
confidence: 79%
“…Immunomodulation (Wu et al, 2007) TNF-a↓, NF-kB inhibited, caspase-3 inhibited Emodin treatment in BALB/c mice with AMI (Song et al, 2012) TNF-a and IL-1b↓, NF-kBp65 inhibited Emodin treatment in EAM in male Lewis rats (Jiang et al, 2014) IL-1b, IL-6, TNF-a, IL-23, and IL-17↓, NF-kBp65 inhibited Emodin treatment in BALB/c mice with viral myocarditis (Shou et al, 2018) PPAR-g and eNOS phosphorylation↑, NO↑ Emodin treatment in HAECs with ischemia-mimetic (Xu et al, 2018b) BMP2, TRAF1, and RELA↓, calcification, and phenotypical transformation of hVICs via the NF-kB signaling pathway…”
Section: References Finding Methodologymentioning
confidence: 99%
“…The study was approved by the Ethics Committee of Tongji Medical College, Huazhong University of Science and Technology (Wuhan, China). Aortic valve leaflets were excised and rinsed according to our previous protocol [15]. Then, tissues were minced and placed in collagenase (150 units/mL) in Dulbecco's Modified Eagle's Medium (HyClone, Logan, UT, USA) for 6–8 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%